2021
DOI: 10.1016/j.nicl.2021.102697
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography abnormalities in adult mild traumatic brain injury: A systematic review

Abstract: Highlights Magnetoencephalography has higher sensitivity than clinical imaging to detect abnormalities in mild traumatic brain injury Excess resting state low frequency power is consistently detected following mild traumatic brain injury. There are widespread magnetoencephalography connectivity changes following mild traumatic brain injury. Machine learning techniques generate high classification accuracy when analysing magnetoencephalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…From a theoretical perspective, oscillations have been argued to play a mechanistic role in the dynamic temporal and spatial organisation of neural activity (Bastos et al, 2015;Buzsaki, 2006;Fries, 2015). Furthermore, perturbations to oscillations are associated with several clinical conditions, including Autism spectrum disorder (Kessler et al, 2016;Seymour et al, 2019), schizophrenia (Kirihara et al, 2012;Thuné et al, 2016) and mild traumatic brain injury (Allen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical perspective, oscillations have been argued to play a mechanistic role in the dynamic temporal and spatial organisation of neural activity (Bastos et al, 2015;Buzsaki, 2006;Fries, 2015). Furthermore, perturbations to oscillations are associated with several clinical conditions, including Autism spectrum disorder (Kessler et al, 2016;Seymour et al, 2019), schizophrenia (Kirihara et al, 2012;Thuné et al, 2016) and mild traumatic brain injury (Allen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although deemed "mild", concussed patients remain symptomatic (characterized by physical, emotional, cognitive, and sleep disturbances) for more than 2 weeks in 50% of cases and up to several months in 5-20% of cases after the initial injury (2). Several neuropsychological studies have reported reduced cognitive efficiency in patients with mTBI, especially in processing speed, executive function, connectivity, attention, and memory (3,4). However, to date, the neurobiological mechanism of post-mTBI cognitive impairment remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lower P3 is also seen in other disorders, i.e., depression (Bruder et al, 2012;Klawohn et al, 2020), schizophrenia (Qiu et al, 2014), bipolar (Wada et al, 2019), attention deficit/hyper-activity (Kaiser et al, 2020), autism (Cui et al, 2017), psychopathy (Gao and Raine, 2009), panic (Howe et al, 2014), and Alzheimer's (Hedges et al, 2016), suggesting that P3 may be a trans-diagnostic factor (i.e., not specific to SUD) related to deficits in P3-associated attentional, working memory, and behavioral updating processes. Similarly, there is evidence for beta as a transdiagnostic rather than SUD-specific factor, as suggested by higher beta in insomnia , psychosocial stress (Vanhollebeke et al, 2022), and Parkinson's (Cagnan et al, 2019), and dysregulated (or decreased) beta in externalizing disorder (Rudo-Hutt, 2015), traumatic brain injury (Allen et al, 2021) and epilepsy (Dharan et al, 2021). In addition, theta deserves more research attention, as it is (like beta) a heritable marker of AUD (Meyers et al, 2021), involved with working memory and executive control (Cavanagh and Frank, 2014), and a well-studied biomarker in depression (Jamieson et al, 2022) and schizophrenia (Hirano and Uhlhaas, 2021).…”
Section: Discussionmentioning
confidence: 99%